Human Physiological Responses to a Single Deep Helium-Oxygen Diving - Bao, Xiao-Chen; Shen, Quan; Fang, Yi-Qun; Wu, Jian-guo (Frontiers in Physiology, 2021)
Objective: To explore whether a single deep helium-oxygen (heliox) dive affects physiological function. Methods: Forty male divers performed an open-water heliox dive to 80 meters of sea water (msw). The total diving time was 280 min, and the breathing helium-oxygen time was 20 min. Before and after the dive, blood and saliva samples were collected, and blood cell counts, cardiac damage, oxidative stress, vascular endothelial activation, and hormonal biomarkers were assayed. Results: An 80-msw heliox dive induced a significant increase in the percentage of granulocytes (GR%), whereas the percentage of lymphocytes (LYM%), percentage of intermediate cells (MID%), red blood cell number (RBC), hematocrit (hCT), and platelets (PLT) decreased. During the dive, concentrations of creatine kinase (CK), myocardial-specific isoenzyme of creatine kinase (CK-MB) in serum and amylase alpha 1 (AMY1) and testosterone levels in saliva increased; by contrast, IgA levels in saliva decreased. Diving caused a significant increase in serum glutathione (GSH) levels and reduced vascular cell adhesion molecule-1 (VCAM-1) levels but had no effect on malondialdehyde (MDA) and endothelin-1 (ET-1) levels. Conclusions: A single 80-msw heliox dive activates the endothelium, causes skeletal-muscle damage, and induces oxidative stress and physiological stress responses, as reflected in changes in biomarker concentrations.